PERAN STATUS KEPEGAWAIAN DALAM MEMODERASI PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN - Dijah Julindrastuti; Iman Karyadi (UPT Penerbitan Universitas Jember)
The purpose of this study was to examine the effect of employment status on job satisfaction and organizational commitment and to examine the effect on employment status role in moderating the influence of job satisfaction on organizational commitment of employees. Samples were employees of non-educational contract status and permanent status at the University of Wijaya Kusuma Surabaya and Malang Islamic University. The sampling technique is done by simple random technique. The size sample of 128 employees comprising 63 contract employees and permanent employees 65 people. The analysis technique used is Independent sample t test and Moderated Regression Analysis. Hypothesis test results showed that employment status has no significant effect on job satisfaction and organizational commitment and employment status does not moderate the effect of job satisfaction on organizational commitment of employees. Only the hypothesis of job satisfaction have a significant effect on organizational commitment are supported.